PH‐Responsive Hybrid Organic–Inorganic Ruthenium Nanoparticles for Controlled Release of Doxorubicin. (24th October 2017) - Buchtelova, Hana; Strmiska, Vladislav; Dostalova, Simona; Michalek, Petr; Krizkova, Sona; Kopel, Pavel; Hynek, David; Richtera, Lukas; Adam, Vojtech; Heger, Zbynek
Abstract: The current study aims at preparing biocompatible hybrid organic–inorganic ruthenium core–shell nanostructures (RuNPs) coated with polyvinylpyrrolidone (PVP) and polyoxyethylene stearate (POES). Thereafter, the core/shell RuNPs are loaded with doxorubicin (to form RuPDox) with a loading efficiency > 60%. RuPDox possesses exceptional stability and pH‐responsive release kinetics with approx. 50% release of doxorubicin at up to 1 h exposure to an acidic endosomal environment. The cytotoxic effects of RuPDox are tested in vitro against breast cancer (MDA‐MB‐231), ovarian cancer (A2780), and neuroblastoma (UKF‐NB‐4) cells. Notably, although RuNPs have slight cytotoxicity only, RuPDox causes a synergistic enhancement of cytotoxicity when compared to free doxorubicin. Significant increase in free radicals formation, enhanced activity of executioner caspases 3/7, and higher expression of p53 and metallothionein is further identified due to the RuPDox treatment. Single‐cell gel electrophoresis reveals no additional contribution of RuNPs to genotoxicity of doxorubicin. Moreover, RuPDox promotes significantly increased stability of doxorubicin in human plasma and pronounced hemocompatibility assayed on human red blood cells. The results imply a high potential of biocompatible hybrid RuNPs with PVP‐POES shell as versatile nanoplatforms to enhance the efficiency of cancer treatment. Abstract : Hybrid organic–inorganic nanoparticles based on ruthenium are developed for efficient loading and pH‐responsive release of the anticancer drug doxorubicin. The nanoparticles enhance doxorubicin‐related apoptotic processes through activation of p53 and metallothionein‐3 while having exceptional biocompatibility in vitro. This work shows a high potential of biocompatible hybrid ruthenium nanoparticles as versatile platform for nanomedicine.